Objective analysis of vision impairments using single trial VEPs - Muthusamy, Hariharan, Dr.; Vikneswaran, Vijean; Sazali, Yaacob, Prof. Dr. (Institute of Electrical and Electronics Engineers (IEEE), 2012)
Link to publisher's homepage at http://ieeexplore.ieee.org/